Antifungal Constituents from the Roots of Piper dilatatum Rich. (24th June 2013) - dos Santos, Ruilan Alves; Ramos, Clécio Souza; Young, Maria Cláudia M.; Pinheiro, Thamilles Gonçalves; Amorim, André M.; Kato, Massuo J.; Batista, Ronan
Abstract : The compounds (+)-(7 S, 8 R )-epoxy-5, 6-didehydrokavain (1 ), flavokavain B (2 ), β -sitosterol (3 ), and stigmasterol (4 ) are reported here as chemical constituents of Piper dilatatum Rich. (Piperaceae). Their structures were determined on the basis of their spectroscopic data ( 1 H and 13 C NMR, MS, and IR). The antifungal activities of pyrone 1 (1 μ g) and chalcone 2 (100 μ g) were determined by means of direct bioautography against Cladosporium cladosporioides and C. sphaerospermum . Results indicate P. dilatatum as a candidate for the development of novel antifungal phytotherapic products as well as point out pyrone 1 as a promising hit compound in the quest for novel antifungal agents.